Potential compaction in two soils of the flat portion of valle del cauca (2012)
Samples from the top 20 cm of two soils in CIAT Palmira (Calciustoll and Haplustoll both vertic mixed loaxny isohipertermic 0.5% slope) used in both secondary forest cover and diverse crops for more than ﬁfty consecutive years were compacted into the apparatus of Richards at two soil moisture contents (O. 1 and 0.5 bar) to compare the point of maximum soil compaction and its inﬂuence in the soil bulk density changes, rate of oxygen diffusion, aeration porosity, saturated hydraulic conductivity and rupture modulus. A complete randomized design with factorial arrangement was used which consisted of 2 soils x 2uses x 2 soil moisture content x 3 repetitions and means separated by Duncan probe. The study showed that high soil content of O.M. do not always prevent soil degradation due to of agricultural machinery traﬂic at high soil moisture contents. Irrespective of soil use, siltier Calciustoll had a slightly more potential to compaction than Haplustol, and continued cultivation of the two soils has made them more susceptible to physical daxnage, because in wet condition compacted to the extreme and showing physical degradation which in practice may result from traﬂic on soils, and in moist state, compacted moderately.